194k views
4 votes
What is the following equation formed when completing the square on Y^2-12y=-27

User Fabianius
by
3.9k points

2 Answers

5 votes

Answer:y^1=3 ,y^2=9 if im wrong sorry im wrong but hope you get an a




User Ali Shahbaz
by
4.7k points
5 votes

Answer:


(y -6)^(2) = 9

Explanation:

Given the function:


y^(2) -12y = -27

To find the completing the square of the above function, we use the following formula:


a^2-2ab+b^2=(a-b)^2. So we have:


y^(2) -12y = -27


y^2-2* x* 6+6^2=-27+6^2\\(y-6)^2=-27+36\\ (y-6)^2=9.

Hope it can find you well.

User James Sapam
by
4.7k points